Happiness at higher education institutions: an empirical study among Malaysian lecturer - Isa, Khairunesa; Palpanadan, Sarala Thulasi (2020)
Lecturers‘ tasks are different from the teachers‘. Flexible working hours and composite work specification sometimes make thier working life unstable and it will indirectly affect their happiness. This study was conducted to identify the triggering factors that affect the happiness of Malaysian academicians‘ happiness. A total of 40 academicians were selected as respondents from three selected university which was under the cluster Comprehensive University, Research University and Focus University. This preliminary study found that the happiness level among Malaysian academicians at Higher Education Institutions were at moderate level with the mean value of 3.118 and standard deviation value of .3791. The university factor (organization) was found to have a moderate higher mean (3.245) than the individual factor (mean = 3.022) and social factor (mean = 2.991). Based on this finding, it can be concluded that work load and job activities have high impacts towards lecturers‘ happiness. The finding also relatively showed that lecturers have interest and passion on specific tasks. Hopefully, this finding can help in producing a criterion on happiness for lecturers at Malaysian public higher education institutions.